Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
Home  >>  CBSE XII  >>  Math  >>  Model Papers
0 votes

Solve : \[ tan^{-1}(x+1)+tan^{-1}(x-1)=tan^{-1}\frac{8}{31}\]

Can you answer this question?

1 Answer

0 votes
  • \( tan^{-1}x+tan^{-1}y=tan^{-1}\bigg( \large\frac{x+y}{1-xy} \bigg) \)
By taking x+1 in the place of x and x-1 in the place of y we get
Substituting in the above formula of \(tan^{-1}x+tan^{-1}y\) we get
\(\Rightarrow\:tan^{-1} \bigg(\large \frac{2x}{2-x^2} \bigg) = tan^{-1}\large\frac{8}{31}\)
\( \Rightarrow \large\frac{2x}{2-x^2}=\large\frac{8}{31}\)
Solving which we get\( x=-8\:\:or\:x=\large \frac{1}{4}\)
But \( x = -8\) is not in principal interval so \( x= \large\frac{1}{4}\)
answered Feb 28, 2013 by thanvigandhi_1
edited Mar 19, 2013 by rvidyagovindarajan_1

Related questions

Ask Question
student study plans
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App